Active Cushing syndrome patients have increased ectopic fat deposition and bone marrow fat content compared to cured patients and healthy subjects: a pilot 1H-MRS study. Issue 5 (November 2018) - Maurice, F; Dutour, A; Vincentelli, C; Abdesselam, I; Bernard, M; Dufour, H; Lefur, Y; Graillon, T; Kober, F; Cristofari, P; Jouve, E; Pini, L; et al.
Abstract : Objective: Glucocorticoid excess is one of the most important causes of bone disorders. Bone marrow fat (BMF) has been identified as a new mediator of bone metabolism. Cushing syndrome (CS) is a main regulator of adipose tissue distribution but its impact on BMF is unknown. The objective of the study was to evaluate the effect of chronic hypercortisolism on BMF. Design: This was a cross-sectional study. Seventeen active and 17 cured ACTH-dependent CS patients along with 17 controls (matched with the active group for age and sex) were included. Methods: The BMF content of the femoral neck and L3 vertebrae were measured by 1 H-MRS on a 3-Tesla wide-bore magnet. Bone mineral density (BMD) was evaluated in patients using dual-energy X-ray absorptiometry. Results: Active CS patients had higher BMF content both in the femur (82.5 ± 2.6%) and vertebrae (70.1 ± 5.1%) compared to the controls (70.8 ± 3.6%, P = 0.013 and 49.0 ± 3.7% P = 0.005, respectively). In cured CS patients (average remission time of 43 months), BMF content was not different from controls at both sites (72.3 ± 2.9% (femur) and 46.7% ± 5.3% (L3)). BMF content was positively correlated with age, fasting plasma glucose, HbA1c, triglycerides and visceral adipose tissue in the whole cohort and negatively correlated with BMD values in the CS patients. Conclusions: Accumulation of BMF is induced by hypercortisolism. In remission patients, BMF reached values of controls. Further studies are needed to determine whether this increase in marrow adiposity in CS is associated with bone loss.